70 years of China's foreign exchange market development: history and experience. Issue 1 (27th July 2020) - Wang, Guogang; Lin, Nan
Abstract : Purpose: The development of China's foreign exchange market and the reform of Chinese yuan (hereinafter "CNY") exchange rate are closely linked with each other. Their respective journey through the past 70 years can both be divided into three historical periods; as follows: China's foreign exchange market underwent a difficult exploration period, a formation and development period and an innovative development period; in the meanwhile, the formation mechanism of CNY exchange rate also witnessed three periods marked successively by a single exchange rate system with administrative pricing, an explorative formation mechanism of CNY exchange rate and a reformed, marketized CNY exchange rate mechanism. Design/methodology/approach: In the present world, the development of almost every country is closely linked to the international community, which is the result of the heterogeneity in system, market, humanity and history, in addition to the differences in natural resource endowments and the diversity in technology, administration, information, experience and diplomacy. International economic exchanges require foreign exchange, which gives rise to the existence and development of the foreign exchange market. Findings: The 70-year history of China's foreign exchange market has proven the need to continue safeguarding national sovereignty and interests of the people, stick to the general direction of serving economic development, adhere to the strategy of steadily and orderly promoting the construction of the foreign exchange market, keep on making innovation in monetary policy operation and unbendingly stay away from any systemic financial risks. Originality/value: During the 70-year history of the new China, as an indispensable economic resource in China's economic development, the foreign exchange mechanism bolstered each stage of economic development and was always an important manifestation of China's economic sovereignty. It is argued that during the 30-year planned economy that preceded reform and opening-up, China pursued a closed-door policy with few international economic exchanges. The subtext of such argument is that China did not have (or hardly had much of) a foreign exchange mechanism during this period, which is clearly in conflict with historical evidence. In fact, although China did not have an open foreign exchange market before the reform and opening-up, it had a clear foreign exchange management system and exchange rate system.